APPLICATION OF COOPERATIVE LEARNING METHOD TO IMPROVE LEARNING OUTCOMES OF RHYTHMIC GYMNASTICS USING RIBBONS IN CLASS VIII STUDENTS OF SMP N 2 MEDAN: PENERAPAN METODE COOPERATIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SENAM IRAMA MENGGUNAKAN PITA PADA PESERTA DIDIK KELAS VIII SMP N 2 MEDAN - Supriyani Siregar, Epi; Nadifa Tarigan, Fatin; Purnama Sari, Ika; Ndruru, Mastawati; Maulana, Maulana (UPMI Proceeding Series, 2024)
The application of cooperative learning in rhythmic gymnastics not only improves students' motor skills, but also provides opportunities to develop social and emotional skills. This research aims to improve the learning outcomes of rhythmic gymnastics using ribbons for class VIII SMP students through the application of the cooperative learning method. The research method used is a quantitative approach with an experimental design, namely pretest-posttest control group design. The research sample consisted of two experimental groups that used cooperative learning methods and a control group that used conventional learning methods. The results showed that there was a significant increase in rhythmic gymnastics skills using ribbons, where the knowledge test score increased from 60% in cycle 1 to 88% in cycle 2, and the performance score increased from 67% to 78%. The conclusion of this research is that the application of the cooperative learning method is effective in improving the learning outcomes of rhythmic gymnastics using ribbons for students, as well as strengthening their social and emotional aspects through interaction in groups